The social media communication of Andalusian interest groups: interaction, politics, and propaganda - Pineda, Antonio; Quintana-Pujalte, Leticia; Rodríguez-López, María; Sánchez-Martín, Marta (Frontiers in Political Science, 2025)
Interest groups, one of the main expressions of the diversity of social interests in the contemporary world, are organizations that serve as channels for bringing social demands to the attention of the political establishment with the aim of influencing the design, discussion, approval, and implementation of public policies. This is achieved through actions directly aimed at public institutions, but also through influence campaigns aimed at public opinion building (i.e., grassroots lobbying). However, little is known about the communication strategies and techniques of interest groups on social media, a crucial field in the current political landscape. This paper focuses on communication as a point of contact between interest groups and institutions, thus filling a research gap. We perform a content analysis of a sample of tweets posted by interest groups from the southern Spanish region of Andalusia, from the perspective of social media interaction, digital political communication, and propaganda. Results indicate that interest groups tend to post one-way messages, that the political and institutional communication techniques employed by these groups reflect a restricted use of digital media, and that the propaganda techniques used aim to construct a favorable public image, but without any connection with explicit political objectives. All of which implies that the communication of these groups is deficient in terms of grassroots lobbying.